The Quality of Wheat Bread With Ultrasonicated and Fermented By-Products From Plant Drinks Production - Bartkiene, Elena; Bartkevics, Vadims; Pugajeva, Iveta; Borisova, Anastasija; Zokaityte, Egle; Lele, Vita; Starkute, Vytaute; Zavistanaviciute, Paulina; Klupsaite, Dovile; Zadeike, Daiva; Juodeikiene, Grazina (Frontiers in Microbiology, 2021)
During plant-based drinks production a significant amount of valuable by-products (BPs) is obtained. The valorisation of BPs is beneficial for both the environment and the food industry. The direct incorporation of the fermented and/or ultrasonicated almond, coconut, and oat drinks production BPs in other food products, such as wheat bread (WB) could lead to the better nutritional value as well as quality of WB. Therefore, in this study, various quantities (5, 10, 15, and 20%) of differently treated (ultrasonicated [37 kHz] or fermented with Lacticaseibacillus casei LUHS210) almond, coconut and oat drinks preparation BPs were used in wheat bread (WB) formulations. Microbiological and other quality parameters (acidity, colour, specific volume, porosity, moisture content, overall acceptability) as well as bread texture hardness during the storage and acrylamide content in the WB were evaluated. Among the fermented samples, 12-h-fermented almond and oat, as well as 24-h-fermented coconut drinks preparation BPs (pH values of 2.94, 2.41, and 4.50, respectively; total enterobacteria and mould/yeast were not found) were selected for WB production. In most cases, the dough and bread quality parameters were significantly (p≤0.05) influenced by the BPs used, the treatment of the BPs, and the quantity of the BPs. The highest overall acceptability of the WB prepared with 20% fermented almond drink preparation by-product (AP), 15% fermented oat drink preparation by-product (OP), and 15% ultrasonicated OP was established. After 96 h of storage, the lowest hardness (on average, 1.2 mJ) of the breads prepared with 5% fermented AP, coconut drink preparation by-product (CP), and OP and ultrasonicated CP was found. The lowest content of acrylamide in the WB prepared with OP was found (on average, 14.7 µg/kg). Finally, 15% fermented OP could be safely used for WB preparation because the prepared bread showed high overall acceptability, as well as low acrylamide content.